Pendapatan Nelayan Perahu di Pesisir Pantai Kecamatan Kabola Kabupaten Alor - Sitriana Awola; Melki Imamastri Puling Tang; Triznawati Triznawati; Ribka Labar; Santorius B.Ilu; Yason Jalapuas; Stevany Belplay; Peterson Kamengfani (Student Research Journal, 2023)
This research was conducted in the coastal area of Kabola District, Alor Regency which aimed to determine the factors that affect the income of fishermen, boats, The number of fishermen samples used was 2 boat fishermen. The results of the study showed that partially the model, fish prices and the number of fish catches had a real effect on the income of boat fishermen in Kabola sub-district, Alor Regency. Meanwhile, simultally the fialibel of capital, labor, experience, fish prices and the number of catches have a real effect on the income of fishermen in Kabola sub-district, Alor Regency.